Attempts to Limit Censoring in Measures of Patient Satisfaction. (December 2020) - Nguyen, Cindy; Kortlever, Joost T P; Gonzalez, Amanda I; Ring, David; Brown, Laura E; Somogyi, Jason R
Background: Measures of patient satisfaction are increasingly used to measure patient experience. Most satisfaction measures have notable ceiling effects, which limits our ability to learn from variation among relatively satisfied patients. This study tested a variety of single-question satisfaction measures for their mean overall score, ceiling and floor effect, and data distribution. In addition, we assessed the correlation between satisfaction and psychological factors and assessed how the various methods for measuring satisfaction affected net promoter scores (NPSs). Methodology: A total of 212 patients visiting orthopedic offices were enrolled in this randomized controlled trial. Patients were randomized to 1 of 5 newly designed, single-question satisfaction scales: (a) a helpfulness 11-point ordinal scale from 0 to 10, (b) a helpfulness ordinal 11-point scale from 0 to 5 (ie, with 1.5, 2.5, etc), (c) a helpfulness 100-point slider, (d) a satisfaction 11-point ordinal scale from 0 to 10, and (e) a willingness to recommend 11-point ordinal scale from 0 to 10. Additionally, patients completed the 2-item Pain Self-Efficacy Questionnaire (PSEQ-2), 5-item Short Health Anxiety Inventory (SHAI-5) Scale, and Patient-Reported Outcomes Measurement Information System (PROMIS) Depression. We assessed mean and median score, ceiling and floor effect, and skewness and kurtosis for each scale. Spearman's correlation tests were used to test correlations between satisfaction and psychological status. Finally, we assessed the NPS for the various scales. Results: Ceiling effects ranged from 29% to 68%. The 11-point ordinal helpfulness scale from 0 to 10 had the least ceiling effect (29%). All of the scales were asymmetrically distributed, with the 11-point ordinal scale from 0 to 5 having the most Gaussian distribution (skew = 0.64 and kurtosis = 2.3). Satisfaction scores did not correlate with psychological factors: PSEQ-2 ( r = 0.04; P = .57), SHAI-5 ( r = 0.01; P = .93), and PROMIS Depression ( r = −0.04; P = .61). Net promoter scores varied substantially by scale design, with higher scores corresponding with greater ceiling effects. Conclusions: Variations in scale types, text anchors, and lead-in statements do not eliminate the ceiling effect of single-question measures of satisfaction with a visit to an orthopedic specialist. Further studies might test other scale designs and labels. Level of Evidence: Diagnostic; Level II